GROWTH RESPONSE OF Melaleuca leucadendron L. EXPLANTS TO VARIOUS CONCENTRATIONS OF WPM MEDIUM AND THIDIAZURON IN VITRO - Azizah Nurul Aulia; Susiyanti; Sulastri Isminingsih; Andi Apriany Fatmawaty (Gunung Djati Conference Series, 2026)
This study aimed to investigate the effects of Woody Plant Medium (WPM) concentration and Thidiazuron (TDZ) on the in vitro morphogenesis response of Melaleuca leucadendron L. leaf explants. The research was conducted from November 2025 to March 2026 at the Plant Physiology and Biotechnology Laboratory, Faculty of Agriculture, Sultan Ageng Tirtayasa University. This research used a factorial randomized block design, consisting of three levels of WPM concentration (¼, ½, and full-strength WPM) and three levels of TDZ concentration (0.25, 0.50, and 0.75 mg L-1). Young leaf explants were cultured under controlled conditions (25 ± 2°C, dark incubation). The fastest explant rolling time 1.0 Week After Planting (WAP) was achieved in the combination of ¼ WPM + 0.25 mg L-1 TDZ. The results showed that WPM concentration significantly affected explant diameter at 6 weeks after planting (WAP), while TDZ concentration significantly affected explant diameter at both 6 and 8 WAP. A highly significant interaction between WPM and TDZ was observed for explant diameter at 8 WAP. The treatment combination of ¼ WPM and 0.75 mg L-1 TDZ produced the highest mean diameter (0,366 cm). A notable finding was the occurrence of direct rhizogenesis in two treatment combinations (¼ WPM + 0.75 mg L-1 TDZ and ½ WPM + 0.50 mg L-1 TDZ), attributed to the auxin-like activity of TDZ under dark incubation conditions.